The exhibitions of Unovis art group in Vitebsk (1920-1922) - Lisovs, Aleksandrs (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
In article to value of the Vitebsk suprematistic exhibitions is certain for becoming of the Kazimir Malevich idea to the all russian organisation Unovis. On the basis of publications from periodicals, Malevich's correspondences and archival documents are specified dates and circumstances of the organization of Vitebsk exhibitions of group. Vitebsk exhibitions were the basis for the organization of its expositions in Moscow, Petrograd, Berlin. They promoted distribution of picturesque system, pedagogical experience, philosophy of the Suprematism. Three Vitebsk exhibitions concern to different stages of evolution of idea of association of adherents of the Suprematism. In the exhibition practice was generated to the collective exhibitor as result of collective creativity.